2022
DOI: 10.3390/s22197318
|View full text |Cite
|
Sign up to set email alerts
|

Multinomial Naive Bayesian Classifier Framework for Systematic Analysis of Smart IoT Devices

Abstract: Businesses need to use sentiment analysis, powered by artificial intelligence and machine learning to forecast accurately whether or not consumers are satisfied with their offerings. This paper uses a deep learning model to analyze thousands of reviews of Amazon Alexa to predict customer sentiment. The proposed model can be directly applied to any company with an online presence to detect customer sentiment from their reviews automatically. This research aims to present a suitable method for analyzing the user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Unlabeled data is easily accessible as compared to labeled data. Unknown or hidden insights can be found that are not possible with supervised learning techniques [17]. Labeling of data might cause a manual error, but, in this case, the chances get lowered [7].…”
Section: B Unsupervised Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlabeled data is easily accessible as compared to labeled data. Unknown or hidden insights can be found that are not possible with supervised learning techniques [17]. Labeling of data might cause a manual error, but, in this case, the chances get lowered [7].…”
Section: B Unsupervised Learningmentioning
confidence: 99%
“…Multiple stakeholders, beginning from the manufacturing of equipment and drugs to insurance providers regulate the price of healthcare [17]. Rising costs demoralize people in different aspects, such as undergoing laboratory tests and www.ijacsa.thesai.org regular visits to health practitioners, which affects patient health.…”
Section: B Rise Up In Healthcare Costingmentioning
confidence: 99%
See 2 more Smart Citations
“…Also based on fuzzy theories, Kaminska et al [ 21 ] proposed an improved KNN using ordered weighted average operators and obtained optimal results in applied aspect-based sentiment analysis. Kaushik et al [ 22 ] used a multinomial naive Bayesian Classifier for text-classification-based sentiment analysis. Erkan [ 23 ] reported an eigenvalue-based algorithm, using the eigenvalues of each sample in the test data concerning the training data to make classifications.…”
Section: Introductionmentioning
confidence: 99%